Cognitive empathy moderates the relationship between affective empathy and wellbeing in adolescents with autism spectrum disorder. Issue 4 (4th July 2019) - Bos, Jason; Stokes, Mark A.
Abstract: Background: Individuals with autism spectrum disorder (ASD) reportedly have reduced cognitive empathy (CE), yet intact levels of affective empathy (AE) when compared to typically developing individuals. To date, no research has examined the implications of this empathic imbalance on personal wellbeing (PWB). Method: Twenty four high-functioning adolescents with ASD ( M age  = 13.21, SD  = 2.83, 14 males) and 24 non-clinical control adolescents ( M age  = 13.10, SD  = 2.73, 15 males) took part in the present study. CE and AE were measured using the interpersonal reactivity index, while PWB was assessed via the personal wellbeing index-school children. Results: Participants in the ASD group scored significantly lower than the control group on measures of CE and AE. Moderated regression analyses revealed that for the ASD group only, CE appeared to moderate the relationship between AE and PWB. Specifically, when CE was low, the relationship between AE and PWB was significant and negative. However, when CE was high, the relationship between AE and PWB was significant and positive. Conclusions: CE appears central to the PWB of those with ASD. Only when CE is high were participants able to experience the positive relationship between AE and PWB. Interventions that target the cognitive dimensions of empathy may improve PWB.